Before Frauenkirke. Delayed Reconstruction Work of Historic German Buildings Destroyed During World War II - Raffaele Amore (Histories of Postwar Architecture)
After the Second World War, several years of allied occupation followed for Germany and began the difficult operations of clearing the rubble and counting the damage to the building and infrastructural heritage of the cities. At the same time, many architects began to question possible intervention strategies, giving rise to an interesting debate, in which the theme of the interpretation of the ruins played a central role. After 1949 the socio-political conditions changed: with the birth of two states the priority became to physically rebuild the two new countries. A massive work of reorganization and rebuilding began, which, city by city, resulted in very diversified operational choices, both in terms of restoration of historic buildings and urban and territorial planning. Once this phase was over, after the 1970s, German scholars in the East as well as in the West began to draw up initial critical-compilatory studies of what had been achieved. In the context of these studies, those of Niels Gutschow and Werner Durth, Josef Nipper and Manfred Nutz and Hartwig Beseler and Niels Gutschow are significant. At the beginning of the nineties of the twentieth century, so even before the reunification, the first reconstruction projects were elaborated dove era e come era of buildings destroyed by the war, such as those of the Römerberg Ostzeile in Frankfurt, the Knochenhaueramtshaus in Hildesheim and the Alte Waage in Braunschweig. The proposed contribution intends to illustrate and critically comment on the motivations that led to the reconstruction of these buildings, framing them in the wider debate that has developed in Germany after reunification following the notorius cases of the reconstruction of the Frauenkirke in Dresden and the Berlin Castle, and the well-known exhibition curated in 2010 by Winfried Nerdinger at the Architekturmuseum of the TU München entitled Geschichte der Rekonstruktion – Konstruktion der Geschichte.